Metal cushion dampers for railway applications: A review. (30th March 2020) - Pérez, Alejandro; Ferreño, Diego; Carrascal, Isidro A.; Polanco, Juan A.; Casado, José A.; Diego, Soraya
Highlights: Metal cushion is a potential novel material to replace polymers in rail pads. Metal cushion outperforms traditional rail pads regarding aging degradation. Design and manufacturing aspects of metal cushions are reviewed. Mechanical performance of metal cushions and modeling procedures are summarized. Recommendations for further research are included. Abstract: Polymeric materials are widely employed to manufacture seat pads to be placed between the rail and the sleeper in railways. However, by their very nature, polymeric materials undergo deterioration and aging when exposed to ordinary environmental conditions. For this reason, metal cushions have been proposed as an alternative to polymer plates. This paper provides a review of the foremost design, manufacturing and mechanical aspects of metal cushions. The most important mathematical models to describe their static and dynamic performance are presented. The paper concludes with some guidelines aimed at suggesting future lines of research.